DESIGN AND CONSTRUCTION OF THE GAMPONG LAMSUJEN INFORMATION SYSTEM USING LARAVEL FRAMEWORK (Case Study: Gampong Lamsujen) - Ari Fikri, M.; Ridwan, Ridwan; Vita Dewi, Sarini (SciencePlus, 2025)
Gampong or Village is part of the Regency government area under the Sub-district which is led by the Village Head. Gampong Lamsujen is located in Lhoong Sub-district and in Aceh Besar Regency is a village that has great potential, including in the fields of plantations and agriculture, not only that, Gampong Lamsujen also has various tourist attractions that can attract tourists to visit, but this information is only known by the surrounding community. With the advancement of technology in the current era, in making it easier to get information about Gampong Lamsujen, it can be made into an information system/website so that outsiders can easily find out information about Gampong Lamsujen. This information system was created using the R&D method to ensure that the system built meets the needs and standards that have been set. The Laravel Framework was chosen as the main design tool because of its ability to accelerate the development process and provide an organized structure in designing the system. Based on the results of the admin/village apparatus and user trials, this product has been proven to be suitable and meets the needs. Thus, this website is used as a source of information for Gampong Lamsujen and the outside community who want to know information about Gampong Lamsujen